1981
DOI: 10.1042/bj1950317
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic analysis of proteins from single bovine muscle fibres

Abstract: A number of single fibres were isolated by dissection of four bovine masseter (ma) muscles, three rectus abdominis (ra) muscles and eight sternomandibularis (sm) muscles. By histochemical criteria these muscles contain respectively, solely slow fibres (often called type I), predominantly fast fibres (type II), and a mixture of fast and slow. The fibres were analysed by conventional sodium dodecyl sulphate/polyacrylamide-gel electrophoresis and the gels stained with Coomassie Blue. Irrespective of the muscle, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

1983
1983
2001
2001

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 30 publications
2
34
1
Order By: Relevance
“…In the present study, MyHC isoform composition differed among the ten skeletal muscles, as shown in previous studies of protein level (Young and Davey, 1981;Young, 1982;Manabe et al ., 1995) and mRNA level determined by multiplex RT-PCR (Tanabe et al ., 1998). Although three fast-type MyHC isoforms have not been distinguished from each other in terms of protein level, the previous studies also showed good correlation of expression between the mRNA level and the protein level of MyHC slow or fast isoforms.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In the present study, MyHC isoform composition differed among the ten skeletal muscles, as shown in previous studies of protein level (Young and Davey, 1981;Young, 1982;Manabe et al ., 1995) and mRNA level determined by multiplex RT-PCR (Tanabe et al ., 1998). Although three fast-type MyHC isoforms have not been distinguished from each other in terms of protein level, the previous studies also showed good correlation of expression between the mRNA level and the protein level of MyHC slow or fast isoforms.…”
Section: Discussionsupporting
confidence: 60%
“…The difference in the expression of MyHC isoforms among muscles varies among mammalian species (Manabe et al ., 1995;Tanabe et al ., 1998). The exclusive expression of MyHC-slow observed in bovine MS is a characteristic of ruminant animals (Young and Davey, 1981;Manabe et al ., 1995), presumably because of their sustained chewing behavior. These observations suggest the flexibility of expression pattern of MyHC isoforms in each muscle in response to a specific physiological condition.…”
Section: Discussionmentioning
confidence: 99%
“…The separation gel had a 5-8% polyacrylamide gradient (Bar and Pette, 1988) and the stacking gel was at 3.5%. To improve resolution, the separation gel also contained a 40% glycerol gradient (Sugiura and Murakami, 1990 (Suzuki, 1977;Young and Davey, 1981;Picard et al, 1994). In the present study, the electrophoresis showed the same MHC 1 content in the equine masseter as in the bovine masseter.…”
Section: Specific Protein Preparationmentioning
confidence: 55%
“…Fast-contracting fibres and muscles are additionally recruited as locomotion begins and speed increases. Although Armstrong's model for division of labour is widely accepted, at least one mammalian muscle, the bovine masseter, contains only slow fibres (Young & Davey, 1981;Talmant et al, 1986) yet is not postural. Instead, the masseter is rhythmically active in chewing.…”
Section: Introductionmentioning
confidence: 98%